Where the deer and the antelope play [compact disc, unabridged] : the pastoral observations of one ignorant American who loves to walk outside - Offerman, Nick, 1970- (Penguin Audio, 2021)
A humorous and rousing set of literal and figurative sojourns as well as a mission statement about comprehending, protecting, and truly experiencing the outdoors, inspired by three journeys undertaken by actor, humorist, and New York Times bestselling author Nick Offerman.